Behavior and Factors Influencing Students Riding Motorcycles Without a License to School - Amalia, Hasna Shofy; Brilianti, Dani Fitria (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
In Indonesia, underage motorcycle riders are frequently found operating vehicles without a valid driver's license, raising significant safety and legal concerns. This study aims to explore the motivations and behaviors of these underage riders, as well as the factors contributing to their non-compliance with traffic regulations. Conducted at SMAN 1 Randudongkal with 114 respondents, the research employed a quantitative descriptive approach. This method systematically analyzes numerical data to provide an in-depth understanding of a population or phenomenon, focusing on descriptive insights rather than causal relationships. Data collection was carried out through a structured questionnaire distributed via Google Forms. The analysis revealed that the primary motivations for students riding motorcycles to school without licenses are "saving time" (16.7%) and "the distance from home is too far" (16.7%). Other contributing factors include "convenience over alternative options" (13.2%), "lack of public transportation" (7.0%), and "peer influence" (2.6%). These findings highlight the need for targeted interventions to address this issue, including improved access to public transportation and enhanced awareness campaigns about traffic safety and legal compliance. This study provides valuable insights into the behaviors and decision-making processes of underage motorcycle riders, serving as a foundation for policymakers and educators to develop effective strategies to mitigate this growing concern.